PELATIHAN KOMPUTER PROGRAM MICROSOFT OFFICE UNTUK ANAK-ANAK DI DUSUN 2 BANJAR HARUM 1 DESA MADUKORO KECAMATAN KOTABUMI SELATAN - Arwinda sulistya Putri; Sri Puji Lestari; Dhea Aristania; Desi Lia Sari; Deni Ardita; Yulizatama Aryantika (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2022)
Computer technology is one of the technologies that are often used in everyday life. However, not all people have access to learn and operate computers. One of them is elementary and middle school-age children. Limited access to computers is one of the factors that cause elementary and junior high school students not to be able to operate computers. The purpose of the Sang Surya Umko 2022 KKN work program by holding this training is to increase the knowledge of children in Dusun 2 Banjar Harum 1 Village about the function of computers and to improve the ability of elementary and junior high school students in Hamlet 2 Banjar Harum 1 in operating Microsoft Office programs. This activity was carried out from August 1, 2022, to August 31, 2022, located in Hamlet 2 Banjar Harum 1, Madukoro Village, North Kotabumi District, North Lampung Regency. The training activities ran smoothly and were enthusiastically welcomed by the participants. The success of this activity is demonstrated by the ability of participants to operate the Microsoft Office Program.